Homelessness and rates of physical dysfunctions characteristic of premature geriatric syndromes: systematic review and meta-analysis. (3rd July 2022) - Suh, Kevin; Beck, Jordan; Katzman, Wendy; Allen, Diane D.
ABSTRACT: Background: Homeless adults may experience accelerated aging, presenting earlier with geriatric syndromes such as falls and functional limitations. Though homelessness is surging in United States, data are scarce regarding rates of physical dysfunctions characteristic of geriatric syndromes experienced in this underserved population. Purpose: Examine associations between homelessness, premature geriatric syndromes, and functional limitations. Methods: Two reviewers independently searched PubMed, CINAHL, and PEDro databases for prognostic studies reporting rates of geriatric syndromes in homeless adults aged 40 years and older. Two reviewers independently performed study selection. Data were extracted for homeless adults and community-dwelling controls regarding age, demographic information, limitations of activities of daily living (ADL) and instrumental ADL (IADL), frailty, and falls the past year. Risk ratio (RR) and 95% confidence interval (CI) were calculated across studies to compare groups. Results: Five studies met predetermined criteria. Meta-analysis revealed greater rates in homeless adults (average age 56) compared to housed adults (average age 78) for ADL limitation (RR = 1.50, 95% CI = 1.37–1.64) and IADL limitation (RR = 1.36, 95% CI = 1.28–1.45). Falls were three times more prevalent in homeless individuals (RR = 3.42, 95% CI = 3.16–3.70). Heterogeneous frailty data did not reach significance (RR = 2.59, 95% CI = 0.90–7.46). Conclusion: Homeless adults have increased risk of premature geriatric syndromes. Limitations in ADL and IADL rates were 30–50% higher than adults with stable housing averaging 20 years older, and fall rates were three times higher than controls averaging 4.5 years older. These results underscore the need for healthcare providers such as physical therapists to address physical dysfunction in homeless adults.